Factors influencing Brand Loyalty for Scarlett Whitening products in Jakarta - Erika Erika; Rodhiah Rodhiah (Sultan Publisher, 2023)
This study intends to investigate the effects of three important variables on brand loyalty for Scarlett Whitening products among Jakartan consumers: brand image, brand experience, and brand trust. The study used a quantitative methodology and a survey method to examine data from 100 customers who had at least three purchases of the product. Structural Equation Modeling (SEM) was used to process the data, and the results made it abundantly evident that all three variables greatly affect brand loyalty. The research is helpful for both corporations and academic scholars. For academics, it offers a well-organized overview of the factors influencing brand loyalty, acting as a valuable starting point for further study. Additionally, it implies that future study should think about varying the research factors and increasing the sample size to obtain more diverse results. The findings provide critical consumer behavior insights for businesses, particularly Scarlett Whitening, and emphasize the necessity to concentrate on enhancing brand image, experience, and trust to increase customer loyalty. The study paves the way for future research that will be more thorough and serves as a roadmap for efficient brand management tactics.